Improving skills in master's degree contexts: New experiences with professionals and craft companies - Saéz-Pérez, Mª Paz; Robles Sánchez, Susana (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This research evaluates the improvements that the use of Active Teaching and Learning Methodologies entails regarding the acquisition of professional skills of future graduates of the Masters dealing with intervention in Architectural Heritage, including product and resource improvements. The objectives address students’ training, oriented toward professional activity, determining the effectiveness of innovation. The real problems were exposed to be faced at a professional level and were solved through different parts, which were developed in different phases. The results obtained allowed us to conclude that teaching and performing practical tasks related to professional competencies are verified as an advance in the subject.